Cost-effective GHG mitigation strategies for Western Australia’s housing sector: a life cycle management approach - Lawania, KKrishna; Biswas, Wahidul (Springer, 2016)
The demand of natural resources for Western Australia’s (WA) housing sector is increasing due to economic and population growth, which will be a challenging task for Australia to achieve its GHG reduction target. This paper has assessed possible GHG mitigation options for Western Australia’s houses, where energy-intensive clay brick walls and single-glazed windows are currently being used. A life cycle management framework has been used to determine cost-effective GHG emissions mitigation strategies. This framework integrates life cycle assessment tool, energy rating tool (AccuRate), and life cycle cost (LCC) analysis in order to ascertain environmentally and economically viable alternative building envelop for constructing a house in WA. The results show that the house made of cast in situ sandwich walls, recycled core materials and double-glazed windows, and equipped with solar energy system for electricity and water heating is the best option. This option has life cycle GHG emissions and LCC saving potentials of 7 and 20 %, respectively.